A bibliometric review of the consequences of narcissism among the top management team (TMT): current trends and future perspectives - Nana Adwoa Anokye Effah; Qinggang Wang; Gabriel Kyeremeh; Octavia Ama Serwaa Otchere (Cogent Business & Management)
This paper adopts a bibliometric approach to review previous literature on how narcissism among TMTs impacts firm outcomes. By extracting data from the Web of Science core database from 2005-2022, the intellectual, social, and conceptual structure of articles in the business and management research domain is examined to ascertain the research activity on narcissism. Results show that the field is gradually advancing with more author and regional contributions. Nonetheless, author collaborations are few, and regional collaborations appear to be more concentrated in some specific regions. Thematic analyses revealed declining and relevant themes requiring further development, while emerging themes were assessed, highlighting avenues for future research. As themes such as auditor narcissism, luxury consumption, and audit quality emerge as niche themes, they highlight advancements in the scope of research within the business domain.